Tripping Points on the Roads to Outwit Terror - Sharan, Yair. author. aut Link
XVII, 205 p. 48 illus., 46 illus. in color.
Keywords: This book assesses potential developments of terrorism and ways to prevent it—the growing threats as new technologies become available — and how the same new technologies may help trap those with potential mal-intent. The drumbeat of terror resonates from everywhere; how can we stop it? What are the tripping points along the road and how can we avoid them? Increasingly more people have access to increasingly more information and increasingly more destructive technologies. In the meantime, increasingly advanced technologies help us create an increasingly safer and more harmonious world. Advantages and disadvantages are accelerating each other. While hybrid threats are intensifying, so are the opportunities to address them. But what are the compromises and how can we mitigate them? This book also looks at the unexpected and often random success and failure of policies to counter the evolving terror threat. The various aspects of the terrorism phenomena are presented in a unique way using scenario vignettes, which give the reader a realistic perception of the threat. The combination of positive and negative implications of emerging technologies is describing what might well be one of the most important dimensions of our common future.